Directive Speech Acts of School Principals toward Teachers at SMA Negeri 1 Banawa: A Sociopragmatic Study - Finarti Finarti; Mohammad Tahir; Agustan Agustan (Journal of Educational Sciences, 2026)
This study examines directive speech acts used by school principals in educational leadership communication. It aims to describe the forms, functions, and social contexts of directive speech acts employed by the principal toward teachers at SMA Negeri 1 Banawa. This research adopts a sociopragmatic approach using a descriptive qualitative method. Data were collected through direct observation, interviews, and recordings of communication interactions between the principal and teachers in various situations, including meetings, coaching sessions, and informal conversations. Data analysis was conducted by identifying types of directive speech acts based on Searle’s theory and interpreting their social contexts through Leech’s politeness principle. The findings reveal that the principal’s directive speech acts take the forms of commands, requests, suggestions, prohibitions, and invitations. Their primary functions are to direct, regulate, and motivate teachers in carrying out their professional responsibilities. Socially, the use of directive speech acts is influenced by power relations, social distance, and communication settings. The principal consistently applies politeness strategies to maintain harmonious relationships and to enhance communication effectiveness within the school environment.